2000
DOI: 10.1210/mend.14.2.0425
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin Antagonists Inhibit Insulin-Stimulated GLUT4 (Glucose Transporter 4) Translocation by Preventing the Formation of Phosphatidylinositol 3,4,5-Trisphosphate in 3T3L1 Adipocytes

Abstract: It has been previously reported that calmodulin plays a regulatory role in the insulin stimulation of glucose transport. To examine the basis for this observation, we examined the effect of a panel of calmodulin antagonists that demonstrated a specific inhibition of insulin-stimulated glucose transporter 4 (GLUT4) but not insulin- or platelet-derived growth factor (PDGF)-stimulated GLUT1 translocation in 3T3L1 adipocytes. These treatments had no effect on insulin receptor autophosphorylation or tyrosine phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
23
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 53 publications
5
23
0
Order By: Relevance
“…Taken together, the above data suggest that Ca 2ϩ , presumably via its effects on calmodulin, plays an important role in the insulin-signaling cascade at the level of PI 3-kinase activation and are consistent with previous reports (17). It may also be inferred from the above data that inhibition of insulin-stimulated Akt phosphorylation by either BAPTA-AM or W13 may be at least partly responsible for the observed inhibition of GLUT4 translocation and glucose uptake.…”
Section: Ca 2ϩ and Insulin Actionsupporting
confidence: 92%
See 2 more Smart Citations
“…Taken together, the above data suggest that Ca 2ϩ , presumably via its effects on calmodulin, plays an important role in the insulin-signaling cascade at the level of PI 3-kinase activation and are consistent with previous reports (17). It may also be inferred from the above data that inhibition of insulin-stimulated Akt phosphorylation by either BAPTA-AM or W13 may be at least partly responsible for the observed inhibition of GLUT4 translocation and glucose uptake.…”
Section: Ca 2ϩ and Insulin Actionsupporting
confidence: 92%
“…Glucose Uptake-Previous studies have suggested that the ubiquitously expressed Ca 2ϩ -binding protein calmodulin is required for the efficient activation of PI 3-kinase by insulin and subsequent activation of Akt (17). Consistent with this, we found that pretreatment of cells with the calmodulin antagonist W13 inhibited insulin-stimulated Akt phosphorylation by 70% (Fig.…”
Section: Ca 2ϩ and Insulin Actionsupporting
confidence: 88%
See 1 more Smart Citation
“…Based upon recent studies of the involvement of calmodulin in insulin signaling, a site of action of calmodulin in cell survival signaling by BDNF downstream of receptor activation, but upstream of PI3K activation, seems likely. Thus, it was shown that calmodulin antagonists have no effect on insulin receptor autophosphorylation or tyrosine phosphorylation of insulin receptor substrate-1, but completely abolish insulin-induced activation of PI3K (51). Further analyses in the latter study showed that calmodulin is essential for the formation of phosphatidylinositol 3,4,5-triphosphate.…”
Section: Calmodulin Activity and Intact Calcium-binding Domains 3 Andmentioning
confidence: 90%
“…The Ca 2ϩ -binding requirements for the biological activities of calmodulin in neurons had not been studied previously, although it had been shown that occupancy of all four Ca 2ϩ -binding domains is required for full activity of calmodulin in other cell types (14,51,56,57). To determine the roles of Ca 2ϩ binding in the neuronal survival-promoting function of calmodulin, we mutated critical asparagine residues in each of the Ca 2ϩ -binding domains of calmodulin.…”
Section: Calmodulin Activity and Intact Calcium-binding Domains 3 Andmentioning
confidence: 99%